Analysis of Optical Radiation Emissions During GMAW Applications - Gursel, A.; Kurt, A. (Металлофизика и новейшие технологии, 2015)
The GMAW (Gas Metal Arc Welding) technique and its radiation emissions are examined in this study. Three commonly used materials in industry, SS304-type stainless steel, A36 low-carbon steel, and T6061 aluminium, are chosen for the tests. The welding is applied at 140 A, and radiation types and luminosities are evaluated for each material. During the welding processes, ultraviolet radiation was the most frequently observed at all parameters; in addition, visible light and infrared radiation, 200—1000 nm on an optical scale, are recorded. The effects of electric currents on the photon energy rates are clearly exhibited. The wavelengths are similar on the SS304 and A36 materials, but higher photon energy and intensity are observed on SS304. Furthermore, for the T6061 aluminium material, the optical radiation emission and peak patterns are totally different from the others, with peaks spiking over the entire range of the optical scale.